Conceptual analysis of the constraining factors impeding sustainable development efforts in Nigeria (International Journal of Sustainable Development & World Policy, 2025)
Besides the well-known challenges hindering the achievement of sustainable development goals (SDGs), such as lack of finance, poverty, insufficient educational and health facilities, out-of-school children, inadequate social amenities, climate change, and environmental issues, this paper identified additional human-related constraints, stemming from moral, social/well-being impediments, along with other educational problems, which significantly reinforce existing obstacles. The paper presents high-impact interventions tailored to enhance the attainment of the SDGs, particularly within the Nigerian context. A notable strength of this work is its systematic prioritization of constraints into four distinct categories: moral, social, educational, and project management issues. These factors were further divided into priority subunits, with significant interventions identified according to the Pareto Principle’s 80/20 rule. The paper highlights the interactions among these subunit constraints, demonstrating their synergistic effects. One major issue highlighted in this paper is the "poverty trap syndrome," a condition where a poor nation, due to development and other constraints, becomes trapped deeper into perpetual poverty and can no longer escape. We elucidated this and other concepts with graphical presentations in this paper. A holistic approach is essential for third-world nations to make meaningful progress toward the SDGs. Addressing factors that impede sustainable development and implementing effective interventions are critical. This paper’s framework aims to mitigate barriers to achieving sustainable development goals, encapsulating the essence of this work. The authors advocate these approaches for macro-development studies and have emphasized that morality, as a co-factor, must be considered inevitable when interventions for developmental issues are undertaken.